1998
DOI: 10.1128/mcb.18.6.3612
|View full text |Cite|
|
Sign up to set email alerts
|

L-DNase II, a Molecule That Links Proteases and Endonucleases in Apoptosis, Derives from the Ubiquitous Serpin Leukocyte Elastase Inhibitor

Abstract: The most widely recognized biochemical change associated with the majority of apoptotic systems is the degradation of genomic DNA. Among the enzymes that may participate in this cleavage, the acidic cationindependent DNase II is a likely candidate since it is activated in many apoptotic cells. To better understand its role, we purified and sequenced a DNase II extracted from porcine spleen. Protein sequencing of random peptides demonstrated that this enzyme is derived from a ubiquitous serpin, the leukocyte el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 34 publications
1
80
0
2
Order By: Relevance
“…For example, some of the enzymes translocate to the nucleus upon receiving an apoptotic signal, that is, endoG from mitochondria and DNaseI from the rough endoplasmic reticulum, 11,12 whereas others, namely L-DNaseII and Helicard, are activated by proteolytic cleavage of their precursors. 13,14 Activation of CAD occurs as a result of proteolysis of its inhibitor ICAD. In proliferating cells, ICAD functions as a CAD-specific chaperone, but upon receiving an apoptotic stimulus, caspases cleave it permitting CAD to degrade chromosomal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some of the enzymes translocate to the nucleus upon receiving an apoptotic signal, that is, endoG from mitochondria and DNaseI from the rough endoplasmic reticulum, 11,12 whereas others, namely L-DNaseII and Helicard, are activated by proteolytic cleavage of their precursors. 13,14 Activation of CAD occurs as a result of proteolysis of its inhibitor ICAD. In proliferating cells, ICAD functions as a CAD-specific chaperone, but upon receiving an apoptotic stimulus, caspases cleave it permitting CAD to degrade chromosomal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Important mechanisms include the proteolysis of an inhibitor as in the case of CAD/ICAD (15), or an acidic pH-dependent 1 Abbreviations: CAD, caspase-activated DNase; DAPI, 4,6-diamidine-2-phenylindole; DEVD-AMC, N-acetyl-Asp-Glu-Val-Asp-aminomethylcoumarin; DTT, dithiothreitol; GFP, green fluorescent protein; ICAD, inhibitor of CAD; PARP, poly(ADP-ribose)polymerase; PBS, phosphate-buffered saline; PMSF, phenylmethanesulfonyl fluoride; TBS, Tris-buffered saline; zVAD, benzyloxycarbonyl-Val-Ala-Asp-(OMe)fluoro-methylketone.…”
mentioning
confidence: 99%
“…Acid endonucleases were originally reported at a variety of sizes [2,[11][12][13][14], and subsequent identification of distinct enzymes has suggested that several unrelated enzymes appear to contribute to the acidendonuclease activity found in mammalian tissues. These include DNase II, L-DNase II, Xib, DNase α and DNase β [1,[15][16][17][18][19]. In addition to these unrelated enzymes, a new homologue of human DNase II has been recently cloned, named DNase IIβ (hence the original enzyme is now termed DNase IIα) [20].…”
Section: Introductionmentioning
confidence: 99%